HUBUNGAN KEMIRINGAN LERENG DAN PENGGUNAAN LAHAN DI SISI BARAT GUNUNG LAWU - Supriyono Supriyono; Djoko Purnomo; MTH Sri Budiastuti (Caraka Tani: Journal of Sustainable Agriculture, 2009)
Purpose shifting of forest dominated with tress for becoming agriculture land of annual cropping can not be implemented in arbitrary slope declivity. The slope declivity above 30% or even 45% obviously needs to be maintained for perrenials plant. Therefore, it is necessary to know about the plant genre existing in many slope levels in western side of Lawu Mountain in order to give recommendation for the society and local government in creating rule directed to the forest and land preservation.The results of the survey show that: 1) the decrease of a place height from about 1500 m usl to 100 m usl and 700 m usl can change the vegetation community of perrenial plant to become more various, 2) the vegetation in the height of 1500 m is dominated by pine then Ceiba sp. and high-land vegetables, 3) the vegetation in the height of about 1000 m usl  is dominated by clove, then followed by several wooden plant and tropical fruit plant, 4) in the lower height that is 700 m usl the vegetation is dominated by bamboo, jackfruit, coconut, Tectona sp., and Swietenia sp., and 5) the use of tilt land for cultivating annual plant happens at the height of 1500 m usl, the vegetation is dominated by high-land vegetables.